Book review David Miller, Fatih Bayram, Jason Rothman and LudovicaSerratrice (Eds.), Bilingual cognition and language: The state of the science across its subfield, John Bejamins: Amsterdam, The Netherlands - Khelifa, Alaeddine (Universitas Muhammadiyah Muara Bungo, 2021)
The present paper reviews the Bilingual cognition and language: the state of science across its subfield edited by Miller, Bayram, Rothman and Ludovicaserratrice (2018). The editor's goal is to provide a general overview of bilingualism and its implications for understanding the brain, language development and processing, and the social and educational aspects of different types of bilingualism. There are 17 chapters of this collection divided into main parts; (1) theoretical accounts, (2) child bilingualism, (3) adult bilingualism, and (4) bilingual cognition, neuroscience, and impairment. Each chapters grouping is dedicated to delineating key concepts in the field of bilingualism.